Biocompatible and Biodegradable Organic Transistors Using a Solid-State Electrolyte Incorporated with Choline-Based Ionic Liquid and Polysaccharide - Jo, Young Jin; Kim, Heyn; Ok, Jehyung; Shin, Yiel-Jae; Shin, Joo Hwan; Kim, Tae Hee; Jung, Youngmee; Kim, Tae-il (WILEY-V C H VERLAG GMBH, 2020)
Biocompatible, biodegradable, and solid-state electrolyte-based organic transistors are demonstrated. As the electrolyte is composed of all edible materials, which are levan polysaccharide and choline-based ionic liquid, the organic transistor fabricated on the electrolyte can be biocompatible and biodegrable. Compared to the other ion gel based electrolytes, it has superior electrical and mechanical properties, large specific capacitance (approximate to 40 mu F cm(-2)), non-volatility, flexibility, and high transparency. Thus, it shows mechanical reliability by maintaining electrical performances under up to 1.11% of effective bending strain, 5% of stretching, and have low operation voltage range when it is utilized in organic transistors. Moreover, the biodegradable electrolyte-based organic transistors can be applied to bio-integrated devices, such as electrocardiogram (ECG) recordings on human skin and the heart of a rat. The measured ECG signals from the transistors, compared to signals from electrode-based sensors, has a superior signal-to-noise ratio. The biocompatible and biodegradable materials and devices can contribute to the development of many bioelectronics.
Keywords: FIELD-EFFECT TRANSISTORS; THIN-FILM TRANSISTORS; GEL GATE DIELECTRICS; CONDUCTING POLYMERS; TEMPERATURE-SENSOR; SKIN; INTERFACE; MEMORY; LAYER